Anti-Candida Potential of Sclareol in Inhibiting Growth, Biofilm Formation, and Yeast–Hyphal Transition - Chaerim Kim; Jae-Goo Kim; Ki-Young Kim (Journal of Fungi, 2023)
Even though Candida albicans commonly colonizes on most mucosal surfaces including the vaginal and gastrointestinal tract, it can cause candidiasis as an opportunistic infectious fungus. The emergence of resistant Candida strains and the toxicity of anti-fungal agents have encouraged the development of new classes of potential anti-fungal agents. Sclareol, a labdane-type diterpene, showed anti-Candida activity with a minimum inhibitory concentration of 50 μg/mL in 24 h based on a microdilution anti-fungal susceptibility test. Cell membrane permeability with propidium iodide staining and mitochondrial membrane potential with JC-1 staining were increased in C. albicans by treatment of sclareol. Sclareol also suppressed the hyphal formation of C. albicans in both liquid and solid media, and reduced biofilm formation. Taken together, sclareol induces an apoptosis-like cell death against Candida spp. and suppressed biofilm and hyphal formation in C. albicans. Sclareol is of high interest as a novel anti-fungal agent and anti-virulence factor.